Long-distance passenger rail services: Review and improvement - Peter Endemann (Spatial and transport infrastructure development in Europe: Example of the Orient/East-Med Corridor, 2019)
The situation of long-distance in Europe rail has faced different developments at literally different speeds since the fall of the Iron Curtain. Relevant central European parts of the OEM Corridor (e. g. Germany, the Czech Republic, Austria and Hungary) first suffered a considerable decline in cross-border long-distance rail traffic due to the emergence of low-cost airlines and the freedom of car purchase in the 1990s. Since the beginning of the millennium and partly following the 2004 accession of Middle and Eastern European countries to the European Union, a slight renaissance of Eurocity trains and market penetration of high-speed rail products can be perceived. The other countries in the eastern part of the corridor have mostly not recovered from the rail decline and lag behind. In Greece, rail development suffers generally from unfavourable conditions (different track gauges and disproportion of land and population distribution) and a lack of innovation, and has thus been negatively impacted by the abovementioned boom of car and air. Its geographical isolation in Europe also plays a role. The political downturn of former Yugoslavia reinforced the situation. For passenger rail along the corridor, the paper argues that considerable improvements in service quality and travel time reduction can be made without doubtful high investment in high-speed rail infrastructure. Moreover, building up existing rail infrastructure may avoid giving up conventional rail services as shown for some high-speed rail cases. – – Der schienengebundene Personenfernverkehr in Europa hat sich seit dem Fall des Eisernen Vorhangs mit buchstäblich unterschiedlichen Geschwindigkeiten unterschiedlich entwickelt. Wichtige mitteleuropäische Teile des OEM Corridors (z. B. Deutschland, Tschechien, Österreich und Ungarn) erfuhren aufgrund des Aufkommens von Billigfluggesellschaften und der 'neuen' Freiheit beim Kauf des eigenen PKW in den 1990er Jahren zunächst einen erheblichen Rückgang des grenzüberschreitenden Schienenpersonenfernverkehrs. Seit der Jahrtausendwende und teilweise nach dem Beitritt mittel- und osteuropäischer Länder zur Europäischen Union im Jahr 2004 ist eine leichte Renaissance der Eurocity-Züge und die Marktausbreitung von Hochgeschwindigkeits- Bahnprodukten zu verzeichnen. Weitere Länder im östlichen Teil des Korridors haben sich oft nicht vom Rückgang der Schieneninfrastruktur erholt und hinken hinterher. In Griechenland sind die Bedingungen für das System Schiene generell ungünstig (unterschiedliche Spurweiten und Missverhältnis bei Siedlungs- und Bevölkerungsverteilung) und mangelnder Innovation und wurde daher durch den oben genannten PKW-Boom und ansteigendes Luftverkehrsaufkommen negativ beeinflusst. Auch die geografische Randlage Griechenlands in Europa spielt eine Rolle. Der politische Abschwung im ehemaligen Jugoslawien verstärkte diese Situation. Der Beitrag legt dar, dass erhebliche Verbesserungen bei der Servicequalität und der Verkürzung der Reisezeiten ohne fragwürdig hohe Investitionen in den Hochgeschwindigkeitsverkehr auf der Schiene erreicht werden können. Darüber hinaus kann durch einen Ausbau der bestehenden Schieneninfrastruktur vermieden werden, den klassischen Fernverkehr aufzugeben, wie die Entwicklung des Hochgeschwindigkeitsverkehrs andernorts in Europa verdeutlicht.
urn:nbn:de:0156-0952081; hdl:10419/213084; https://econpapers.repec.org/RePEc:zbw:arlfob:12
Keywords: 710; long-distance transport; passenger rail; high-speed rail; integration; conventional rail; Schienenpersonenfernverkehr; Hochgeschwindigkeitsverkehr; Integration; klassischer Fernverkehr